Metodología para la elaboración de los reajustes de precios en proyectos de edificación de la Constructora JOF - González-Quirós, Luis Fernando (Instituto Tecnológico de Costa Rica, 2017)
The proposed Project aims to develop a methodology for the calculation and make of price adjustments in the contracts of civil construction projects, such as public buildings developed by a construction company. One of the main reasons for this Project is to make available to the construction company a tool that allows calculations of the readjustments of the projects handled by the company, also using correctly all the variables involved to obtain the readjustments. It is intended to associate the influence of the amount obtained in the readjustments for each work progress bill and the total cost of the work against the real value of the raw materials involved in the development of a Project in a given period of time since Delivered the offer of the work in the opening of a tender until the date of execution of the same. In developing the measurement of the readjustments of the company's construction contracts, basically the price indices delivered by the National Institute of Statistics and Censuses, as well as data of Minimum Wages of the Ministry of labor, and arduous investigation in bibliographic sources and field interviews with experts in the field. It is intended to present a tool to obtain the readjustments in the future projects of public works of the construction company. Finally, the tool will be presented using an electronic spreadsheet that seeks to meet the requirements and needs of the company.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Precios; Construcción; Proyectos; Costos; Materia prima; Licitaciones